The Efficacy of Virtual Reality in Climate Change Education Increases with Amount of Body Movement and Message Specificity - Anna C. M. Queiroz; Géraldine Fauville; Adina T. Abeles; Aaron Levett; Jeremy N. Bailenson (Sustainability, 2023)
Climate change impacts are felt globally, and the impacts are increasing in severity and intensity. Developing new interventions to encourage behaviors that address climate change is crucial. This pre-registered field study investigated how the design of a virtual reality (VR) experience about ocean acidification could impact participants’ learning, behavior, and perceptions about climate change through the manipulation of the experience message framing, the sex of voice-over and the pace of the experience, and the amount of participants’ body movement. The study was run in 17 locations such as museums, aquariums, and arcades in the U.S., Canada, the U.K., and Denmark. The amount of body movement was a causal mechanism, eliciting higher feelings of self-efficacy while hindering learning. Moreover, linking the VR narrative about ocean acidification linguistically to climate change impaired learning compared to a message framing that did not make the connection. As participants learned more about the experience, they perceived the risks associated with ocean acidification as higher, and they were more likely to engage in pro-climate behavior. The results shed light on the mechanisms behind how VR can teach about ocean acidification and influence climate change behavior.